IMPLEMENTATION OF TEACHING MATERIALS USING A REALISTIC MATHEMATICS EDUCATION APPROACH IN PRIMARY STUDENT MATHEMATICS COMMUNICATION - Rabbani, Sylvia; Muftianti, Agni (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2020)
The main problem in this study is the lack of student communication skills and the lack of RME-based teaching materials that use used goods as a learning medium. The long-term objective of the research to be carried out is to support quality improvement and development of basic and regional education policies at the local and national levels through improving the quality of Indonesia's young generation of hope. The purpose of this study was to obtain an overview of the results of the implementation of teaching materials